Pengembangan multimedia pembelajaran untuk mengembangkan aspek kognitif anak - Henny Riska Pratiwi; Christina Ismaniati (Universitas Negeri Yogyakarta, 2017)
Penelitian ini bertujuan: (1) menghasilkan produk multimedia pembelajaran untuk mengembangkan aspek kognitif pada materi mengenal bilangan anak Palm Kids School Yogyakarta, dan (2) mengetahui tingkat kelayakan produk yang dikembangkan. Penelitian ini merupakan penelitian dan pengembangan yang mengacu pada langkah-langkah desain pengembangan Allesi Trollip, yang dikelompokkan atas tiga prosedur pengembangan, meliputi: (a) planning, (b) design, dan (c) development yang dilengkapi dengan komponen atribut mencakup standards, ongoing evaluation, dan project management. Penelitian ini menghasilkan produk multimedia pembelajaran yang memenuhi kriteria dan dinyatakan layak sebagai media pembelajaran. Skor penilaian kelayakan produk melalui uji alpha pada ahli materi adalah 3,4 (layak) dan pada ahli media adalah 3,36 (layak). Uji beta menunjukkan skor hasil penilaian guru kelas K1 sebesar 3,7 (sangat layak). Kelayakan produk multimedia pembelajaran pada peningkatan perkembangan kognitif didukung oleh peningkatan perolehan skor hasil belajar kognitif anak K1 yang diketahui dari hasil pretes dan postes anak adalah sebesar 8,7.Kata kunci: multimedia pembelajaran, kognitif anak DEVELOPING TEACHING MULTIMEDIA TO IMPROVE THE COGNITIVE ASPECTS OF THE CHILDRENAbstractThis study aims to: (1) produce learning multimedia improve the cognitive aspects of the children of Palm Kids School Yogyakarta in understanding numbers, and (2) determine the feasibility level of the developed product. This research was research and development refering to the steps of developmental design proposed by Allesi and Trollip. The design was classified into three developmental procedures including: (a) planning, (b) design, and (c) development, completed with attributes of component including standards, ongoing evaluation, and project management. This study produced teaching multimedia which meet the criteria and the product is declared feasible as teaching media based on the score of product’s feasibility assessment through alpha test by material experts which is at 3.4 (feasible) and by media expert at 3.36 (feasible). Furthermore, the beta test conducted by teacher of K1 class showed the score of 3.7 (highly feasible). The product’s feasibility assessment of the teaching multimedia in improving the development of cognitive aspects was supported by the score of cognitive learning outcomes of the children in K1 class was observed by pre-test and post-test showing 8.7.Keywords: teaching multimedia, children’s cognitive